Pengaruh Pola Asuh Orang Tua Milenial terhadap Hasil Belajar Al-Qur’an Hadist Peserta Didik Kelas V Madrasah Ibtidaiyah - Siti Jumiati; Irma Ariyanti (Rihlah Review: Jurnal Pendidikan Islam, 2022)
This study aims to answer the parenting pattern of millennial parents of fifth grade students; learning outcomes of Al-Qur'an Hadith for V class; the influence of millennial parenting patterns on the learning outcomes of fifth grade students at MI Ma'arif NU Bantengputih Academic Year 2021/2022. This research is a quantitative research. The sample in this study was 17 students. Data collection uses a questionnaire distributed to parents to determine the effect of millennial parenting on the learning outcomes of fifth grade students at MI Ma'arif NU Bantengputih Lamongan for the 2021/2022 academic year using the percentage formula. While collecting learning outcomes data using the average value of the daily test results of the Al-Qur'an Hadith. The data analysis technique used is product moment correlation. The results of this study indicate that based on data analysis of variables (X=71%) and (Y=82%). Then statistical calculations using the product moment correlation formula obtained significant results, namely (r count > r table 0.683 > 0.482), which includes a coefficient interval of 0.60-0.799, so it can be said "there is a correlation with a high level of parenting between millennial parents and learning outcomes of fifth graders at MI Ma'arif NU Bantengputih Lamongan